Pemberdayaan Masyarakat Desa dengan Pelatihan Perencanaan Pembangunan Inklusif Bagi Kepala Desa di Kabupaten Purwakarta - Nailufar, Faza Dhora; Sijabat, Saut Gracer; Saksono, R.N Afsdy; Taqiyya, Aghitsna Putri (LPPM Universitas Narotama, 2024)
One of the vulnerable groups that is often less considered in the development process is the disability group. this is because there is still a negative stigma and stereotype against them. For this reason, in 2016, the government has issued regulations related to respect and proper treatment of disability groups through Law No.8 of 2016. One way to optimize the involvement of disability groups in development is through the Inclusive Village or Disability Friendly Village program. Inclusive villages are built by involving the support and participation of village communities, by affirming minority, poor, vulnerable and marginalized groups. This community service program aims to help the Purwakarta Regency Government to encourage the integration of the principle of inclusiveness in village development planning by encouraging bureaucrats, especially village bureaucrats (Village Heads) to actively integrate the principle of inclusiveness in village development planning. This community service activity targets Village Heads throughout Purwakarta Regency. The results of this community service activity on the topic of Inclusive Development Planning were well carried out, where the response of the village heads to the activities that had been carried out was considered very good, this can be seen from the increased pre-test and post-test survey results, evaluation of the implementation of activities, suggestions and input from participants on the implementation of the program.